The influence of environmental cognition on green consumption behavior - Xie, Chi; Wang, Ru; Gong, Xiaoxiao (Frontiers in Psychology, 2022)
With rising consumption and environmental problems, there is an increasing need for green consumption. From a micro perspective, the influence of environmental cognition on consumers’ green consumption behaviors and the related mechanisms are examined through multilayer linear analysis and 2010 China General Social Survey (CGSS) microdata with the theory of planned behavior (TPB) as the model framework. The study shows that (1) environmental cognition positively influences attitudes toward green consumption, green consumption subjective norms, and green consumption perceived behavioral control, which leads to increased intentions to engage in green consumption and actual green consumption behaviors. Environmental cognition can either promote the intention toward and lead to green consumption behavior or directly promote green consumption behavior. (2) The more developed a region’s economy is, the stronger people’s attitudes toward green consumption will be; additionally, the greater the perceived external pressure to engage in green consumption becomes, the greater the likelihood that people will develop the intention to engage in green consumption behavior. Regional environmental quality inhibits green consumption intention to a certain extent. (3) The influence of environmental cognition on green consumption shows regional heterogeneity.